A literatura infantil no desenvolvimento da narrativa em crianças oriundas de contextos de baixa escolaridade - Costa, Ana Amélia Sanches (2009)
This research aimed to understand the development of the organization of oral narrative in children of 5 years old, from low-income contexts, through children's literature. Stories for children were previously selected to insert, in the context of the classroom, discussions on the values which were explored in the texts and are related to reality in which the students are inserted. The work in the classroom was also mediated by text recalls. Theoretically this investigation is based on the Theory of Socio-Historical-Cultural Activity (Vygotsky, Leontiev, Engeström) and on Bakhtinian dialogism, in order to discuss the shared production of meanings in an activity of language; on Koch & Travaglia s (1990/2008) and Bronckart s studies (1999), in order to observe the questions concerned to text: types of discourse, sequences, coherence, thematic content and lexical choices (nouns, verbs, deictics); on Orsolini (2005), Brookfield & Preskill (1999) e Kerbrat-Orecchioni (2006), in order to analyze the speech turns (quantity and types) during interaction. Critical Research of Collaboration oriented the methodology, which was designed to organize the development of a joint work between researcher and teacher, but, in fact, it did not occur. According to Magalhães (2007a), this approach aims to intervene in the context, transforming it and creating spaces for joint construction, which happened, indeed, between researcher and students. A collaborative-argumentative space was created by building a space of understanding, that involves all participants in a discussion in order to the researcher rethink her choices and to the students reorganize their participation in discussions during the storytelling circle time , led by the researcher. The study was conducted in a public school of early childhood education in Mairiporã. Initially, interviews were conducted with the teacher and the principal to comprehend the context of the institution, the reality of that community and the children s specific needs. The data were collected through audio recordings (interviews to the principal and the classes) and through notes and diaries (conversations with the teacher). Three classes were selected for analysis. The results revealed that both the recall and the discussion of values created a space / context for developing the organization of the narrative, since the creation of a collaborative interactional pattern in which all shared the same object of activity and also showed motivation to work